Estudio del levantamiento de cargas del personal de la construcción URBYCON S.C. - Moreno Pilatasig, César Pablo (2018)
The purpose of the project is to make known the ergonomic risk that affects the tasks of cargo handling carried out by the employees of the URBYCON S.C. Construction Company, in the area of building and metal-mechanics. This objective is to improve safety in each of the employees through determining the existence of risk by proposing a minimization alternative, where it is intended to collect, select the scientific theoretical information available in different sources and from various authors in order to support the research; starting with a methodology that is adapted to the object under investigation with a reference document about the maximum load lifting per person based on the results of the data obtained, so the support of a methodology based on bibliographic, documentary, and field research is required in order to collect data that serves as fundamental contributions to the development of the investigation; therefore the importance of the project lies in the fact of it will be achieved to improve labor safety standards as well as compliance with laws and regulations around the issue, providing confidence and security in the performance of the workers.